Investigating the impact of nanoparticle geothermal silica loading on the mechanical properties and vulcanization characteristics of rubber composites - Syabani, Muh Wahyu; Rochmadi; Perdana, Indra; Prasetya, Agus (Communications in Science and Technology, 2023)
The present study investigates the effects of nanoparticle geothermal silica (NGS) on the mechanical properties and vulcanization characteristics of rubber compounds with various filler loadings. The rubber compounds were filled with 0, 20, 30, and 40 phr of silica. The properties of NGS were analyzed using transmission electron microscopy, particle size analyzer, and BET surface area analysis to examine its morphology, size distribution, and surface area. The mechanical properties and vulcanization characteristics of the rubber compounds reinforced with NGS were evaluated using a universal testing machine and moving die rheometer. The results showed that NGS possessed the primary particle sizes below 20 nm and a surface area of 168.35 m2/g. The interaction between silica and rubber determined the modulus of the rubber composites and the vulcanization characteristics. The tensile strength of the rubber compounds, meanwhile, showed a significant increase more than threefold as the filler loading increased from 0 phr to 30 phr, followed by a slight decline at 40 phr loading. The addition of 20 phr of silica led to a prolonged scorch time compared to the filler-free compound due to the adsorption of activators and accelerators. However, the scorch time decreased after reaching 30 phr of silica loading, which could be attributed to the higher amount of bound rubber covering a portion of the silica surface, thereby reducing its ability to adsorb the activator. The presence of silica with good thermal conductivity enabled a better heat transfer during the vulcanization process, resulting in shorter curing times for higher loading. Rubber compounds with an NGS loading of 30 phr demonstrated a favorable balance between filler-rubber interactions, vulcanization characteristics, and mechanical properties in the rubber compounds.